Enhanced Recovery After Surgery: It's Time to Change Practice!. (February 2016) - Steenhagen, Elles
Perioperative surgical care is undergoing a paradigm shift. Traditional practices such as prolonged preoperative fasting (nil by mouth from midnight), bowel cleaning, and reintroduction of oral nutrition 3–5 days after surgery are being shunned. These and other similar changes have been formulated into a protocol called Enhanced Recovery After Surgery (ERAS) pathway. It is a multimodal perioperative care pathway designed to achieve early recovery after surgical procedures by maintaining preoperative organ function and reducing the profound stress response following surgery. The key elements of an ERAS protocol include preoperative counseling, optimization of nutrition, standardized analgesic and anesthetic regimes, and early mobilization. The recent literature is heavily influenced by colorectal surgery, but the principles are now being applied to a wide range of disciplines. As they challenge traditional surgical doctrine, the implementation of ERAS guidelines has been slow, despite the significant body of evidence indicating that ERAS guidelines may lead to improved outcomes.